(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2023)
Michelle Zauner’s Crying in H Mart is an evocative memoir of an Asian- American woman who struggled to accept her mixed heritage. A major turning point in her life was having to deal with grief over the loss of a loved one through the help of food. While food has frequently been studied in relation to grief and identity, the ways in which these intersect is less common and warrants further exploration. Given the multiplicity of identities embodied by the protagonist and their often-conflicting nature, the researchers employed Herman’s dialogical self theory (DST) as a framework to better understand her journey towards self-discovery and acceptance. With each identity being given a voice of their own, the constant negotiation among them became apparent and the role played by food in the process was also highlighted. Findings indicate that food as a primary marker for Michelle to reclaim her own heritage and identity was emphasised repeatedly in the memoir. It reinforces the notion that food is affective in nature because it is capable of evoking emotions and memories that could (re)shape one’s identity. While Michelle initially rejected her Korean (Asian) heritage, she begins to reclaim and embrace it while reconnecting with her ailing mother through their shared affection for Korean food. It is through her love of Korean food that Michelle is able to gradually embrace one of the major changes in her life and subsequently overcome the identity crisis that has been troubling her.